1998
DOI: 10.1071/ah980078
|View full text |Cite
|
Sign up to set email alerts
|

A review of hospital medical record audits: Implications for funding and training

Abstract: As new methods of electronic data storage and distribution appear in hospitals, newchallenges in protecting confidentiality have emerged. At the same time, demands for?seamless? care and the desire to share information between clinicians are motivatinghospitals to relax barriers to the transfer of patient information.Increasing numbers of users at multiple sites compound the difficulty of ensuringinformation systems security. Hospital policy may demand that requests by patientsto restrict the distribution of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…For example, from recoding 4000 records, the 3 hospitals involved were found to have failed to identify $176,805 of potential funding. Stevens et al (1998) reviewed coding in 7 Western Australian hospitals in 1997 and found that coding errors accounted for a loss of nearly $400,000 per year per hospital. In contrast to the loss of funding experienced by Australian hospitals, in the United States Hsia et al (1988) sampled 239 hospitals and found that 61.7% of coding errors favoured the hospital, meaning that hospitals were receiving a higher net reimbursement than was supportable by the medical records.…”
Section: Issues Of Documentation Coding and Costmentioning
confidence: 99%
“…For example, from recoding 4000 records, the 3 hospitals involved were found to have failed to identify $176,805 of potential funding. Stevens et al (1998) reviewed coding in 7 Western Australian hospitals in 1997 and found that coding errors accounted for a loss of nearly $400,000 per year per hospital. In contrast to the loss of funding experienced by Australian hospitals, in the United States Hsia et al (1988) sampled 239 hospitals and found that 61.7% of coding errors favoured the hospital, meaning that hospitals were receiving a higher net reimbursement than was supportable by the medical records.…”
Section: Issues Of Documentation Coding and Costmentioning
confidence: 99%
“…Organisational factors that the Australian NCCH believes may impact upon coding quality include: communication with clinicians; ongoing coder education; review of the coding and documentation process by peers or a superior; coder environment and workload; availability of reference materials to guide code allocation; ongoing coder education; and resource support from management (Williamson et al 1999). These appear to be founded on results from Australian and American studies which recognised the importance of ongoing education for quality coding, such as induction programs for new coders (Groom 2000;Hassan, Meara & Bhowmick 1995;Osborn 1999;Stevens, Unwin & Codde 1998, Thompson & Koch 1999, and to reflect findings from other studies (Demlo & Campbell 1981;Green & Benjamin 1986;Mehanni et al 1995). Several authors have further advocated the use of credentialled staff, in-service education, initial orientation and training, and appropriate communication and interaction between coders and healthcare professionals (Fletcher 2002;Mears et al 2002;Waterstraat 1990).…”
Section: Introductionmentioning
confidence: 97%
“…It has long been argued that variable investment in coding effort across the state-based public hospital systems has led to inconsistencies in data quality in some areas (Michel 2008). Despite this, data audits conducted in Victoria have shown the data to be valid and reliable (Henderson, Shepheard & Sundararajan 2006), and Western Australia and Queensland have taken steps based on auditors' comments to improve the quality (Stevens et al 1998;Logan et al 2006).…”
Section: Resultsmentioning
confidence: 99%